Unitary caring science : philosophy and praxis of nursing - Watson, Jean, 1940- (University Press of Colorado, 2018)
"A look at caring and healing as sacred practice with a discussion of the evolution from Caring Science toward Unitary Caring Science which reflects the maturing discipline. Unitary Caring Science offers a personal and professional path that brings love, energy, spirit, and meaning into nurses' lives"--Provided by publisher.